Critical thinking an exploration of theory and practice - Moon, Jennifer A. (Routledge, 2008)
Explores the critical thinking and provides guidance for improving student learning and supporting the teaching process. This book covers various themes including approaches to critical thinking with an emphasis on practical basis; links between learning, thinking and writing; the place of critical thinking alongside other academic activities